2011
DOI: 10.1007/s12010-011-9447-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving Phytase Enzyme Activity in a Recombinant phyA Mutant Phytase from Aspergillus niger N25 by Error-Prone PCR

Abstract: The mutant acid phytase (phyA ( m )) gene was modified by random mutagenesis to improve enzymatic activity by using an error-prone PCR (ep-PCR) strategy. The mutated gene was linearized and inserted into plasmid vector pPIC9K and transformed by electroporation into Pichia pastoris GS115. A single transformant, PP-NP(ep)-6A, showing the strongest phytase activity from among the 5,500 transformants, was selected for detailed analyses. Southern blot analysis of the mutant yeast transformant showed that phyA ( ep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Each assay was performed in triplicate. The V max values were converted to K cat value, by normalizing the enzyme concentrations by the molecular mass of the monomer [8,19].…”
Section: Expressed Phytases Kinetic Parametersmentioning
confidence: 99%
“…Each assay was performed in triplicate. The V max values were converted to K cat value, by normalizing the enzyme concentrations by the molecular mass of the monomer [8,19].…”
Section: Expressed Phytases Kinetic Parametersmentioning
confidence: 99%
“…The E6 strain was determined as the most potential strain in biodegradation with 29.3% raising ratio which is comparable with a study by Mao on beta-1,3-1,4-glucanase from Bacillus altitudinis 21 that resulted in improved activity by 48.6%, and also the study by Liao for Recombinant phyA Mutant Phytase from Aspergillus niger N25 that showed 29% improvement. 30 However, in a study by Loo on Epoxide Hydrolase from A. radiobacter using error-prone PCR and DNA shuffling, the mutants gained up to 13-fold improved enantioselectivity toward pNPGE and at least three other epoxides. 17 In the study by Zuo on serine hydroxyl methyl transferase gene from Escherichia coli strain AB90054 using DNA shuffling method, a mutant namely 3E7 showed 8-fold increase in enzyme activity and 41-fold increase in enzyme productivity compared with its wild-type parent.…”
Section: Biodegredation Of Diazinonmentioning
confidence: 99%
“…Tang and his team employed directed evolution and site-directed mutagenesis approaches on the Aspergillus niger N25 phytase gene and, among all of the mutants obtained, the double mutant Q172R/K432R showed 40% improvement in thermostability over that of the PP-NP ep -6A (the mutant that had been obtained through error-prone PCR in their previous study) at 80 • C for 10 min [24]. The half-life of Q172R/K432R showed a 6.8 min enhancement over that of PP-NP ep -6A.…”
Section: Aspergillus Phytasesmentioning
confidence: 99%